Divergent evolution of membrane protein topology: The Escherichia coli RnfA and RnfE homologues - Sääf, Annika (The National Academy of Sciences, 1999)
Although the molecular evolution of protein tertiary structure and enzymatic activity has been studied for decades, little attention has been paid to the evolution of membrane protein topology. Here, we show that two closely related polytopic inner membrane proteins from Escherichia coli have evolved opposite orientations in the membrane, which apparently has been achieved by the selective redistribution of positively charged amino acids between the polar segments flanking the transmembrane stretches. This example of divergent evolution of membrane protein topology suggests that a complete inversion of membrane topology is possible with relatively few mutational changes even for proteins with multiple transmembrane segments.